Outside the government: Why ethnic parties fail to join the post-communist cabinets - Sergiu Gherghina; George Jiglău (Institut für Ost- und Südosteuropaforschung (IOS), 2013)
This article seeks to identify the causes impeding the ethnic parties to participate in the post-communist coalition governments. We conduct a cross-national and longitudinal analysis in which we take into account all the elections in which the ethnic parties gained parliamentary representation. With 44 cases over two decades - the party in election is the unit of analysis - and Qualitative Comparative Analysis (QCA) as method of analysis, this study bears theoretical and empirical implications. The key findings illustrate that leadership stability (or rigidity) and the involvement in particular issues of representation can drive the ethnic parties out of government. This combined effect prevails against other factors such as the pivotal role, splits or mergers, electoral strategies (alliances or radical discourses), or incumbency.
urn:nbn:de:101:1-201312022923
Keywords: D72; D74; D79; 330; ethnic parties; government coalitions; organizational change; post-communism